Pengaruh Social Media Marketing, Brand Ambassador, dan Brand Image Terhadap Keputusan Pembelian Produk Skincare Azarine Cosmetic (Studi Pada Mahasiswa Universitas Trunojoyo Madura) - Yulis Alfia; Deykha Aguilika (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
This research aims to determine the influence of social media marketing, brand ambassadors¸ and brand image on purchasing decisions for Azarine Cosmetic skincare products. The research method used is a quantitative research approach. The data used are primary and secondary data. The sample used in this research was 100 respondents using non-probability sampling techniques and using purposive sampling techniques. The characteristics of the sample used were Trunojoyo Madura University students who had purchased and used Azarine Cosmetic skincare products. Data collection was carried out through distributing questionnaires and processing the data in this study using SPSS Version 27. Partial test results show that Social media marketing has a significant influence on purchasing decisions, Brand ambassadors do not have a significant influence on purchasing decisions, Brand image has a significant influence on purchasing decisions. The simultaneous test shows that social media marketing, brand ambassador, and brand image together have a significant influence on purchasing decisions.